Deep Ultraviolet Mapping of Intracellular Protein and Nucleic Acid in Femtograms per Pixel - Cheung, Man C. (2011)
By using imaging spectrophotometry with paired images in the 200- to 280-nm wavelength range, we have directly mapped intracellular nucleic acid and protein distributions across a population of Chinese hamster ovary (CHO-K1) cells. A broadband 100× objective with a numerical aperture of 1.2NA (glycerin immersion) and a novel laser-induced-plasma point source generated high-contrast images with short (~100 ms) exposures and a lateral resolution nearing 200 nm that easily resolves internal organelles. In a population of 420 CHO-K1 cells and 477 nuclei, we found a G1 whole-cell nucleic acid peak at 26.6 pg, a nuclear-isolated total nucleic acid peak at 11.4 pg, and, as inferred by RNase treatment, a G1 total DNA mass of 7.4 pg. At the G1 peak we found a whole-cell protein mass of 95.6 pg, and a nuclear-isolated protein mass of 39.3 pg. An algorithm for protein quantification that senses peptide-bond (220-nm) absorbance was found to have a higher signal-to-noise ratio and to provide more reliable nucleic acid and protein determinations when compared to more classical 280-nm/260-nm algorithms when used for intracellular mass mapping. Using simultaneous imaging with common nuclear stains (Hoechst 33342, Syto-14, and Sytox Orange), we have compared staining patterns to deep-UV images of condensed chromatin and have confirmed bias of these common nuclear stains related to nuclear packaging. The approach allows absolute mass measurements with no special sample preparation or staining. It can be used in conjunction with normal fluorescence microscopy and with relatively modest modification of the microscope.